ON THE UNIFORM APPROXIMATION OF AN INNER FUNCTION - Pandeski, Nikola (Matematichki Bilten, 2002)
The inner function \((-1+z1-z)\) we approximate uniformly in the unit disk by interpolating Blaschke products.